1999
DOI: 10.1021/js980338f
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a method for the analysis of a pharmaceutical preparation by near‐infrared diffuse reflectance spectroscopy

Abstract: A near-infrared (NIR) spectroscopic method based on the use of a fiber optical probe for the analysis of a commercially available pharmaceutical preparation is proposed. The analyte is identified by comparison with a second-derivative spectral library, using the correlation coefficient as the discriminating parameter. Once a sample has been positively identified, the active principle is quantified with partial least-squares (PLS) calibration. The proposed method was validated for use as a control method; to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
(10 reference statements)
0
27
0
2
Order By: Relevance
“…Another area of interest is determining drug content in tablets, or content uniformity [11][12][13][14][15][16]. The method of choice for content uniformity of dosage forms in the pharmaceutical industry is high-performance liquid chromatography (HPLC), although ultraviolet (UV) spectroscopy is also used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another area of interest is determining drug content in tablets, or content uniformity [11][12][13][14][15][16]. The method of choice for content uniformity of dosage forms in the pharmaceutical industry is high-performance liquid chromatography (HPLC), although ultraviolet (UV) spectroscopy is also used.…”
Section: Introductionmentioning
confidence: 99%
“…[19] provide guidance for validating assays, but this guidance is strongly based on experiences with chromatographic assays. A recent article by Blanco et al [16] has served to bridge the gap between NIR and chromatographic assay validations by using many of the terms familiar to the pharmaceutical industry. This article presents the results obtained from validation samples in terms of accuracy and also presents assay repeatability results.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that NIR spectroscopy [4,10,11,[20][21][22][23][24][25][26][27][28][29][30][31][32][62][63][64] has now entered a mature stage of development and is currently the most efficient method of performing both qualitative and quantitative analysis; this method can also be used to characterize the particle characteristics, including the sizes of solid samples. Section II.…”
Section: Discussionmentioning
confidence: 99%
“…As the reflectance of solid samples varies with the concentration, the absorptivity and the scattering coefficient according to the Kubelka Munk theory [22], the NIR spectrum of a solid material depends both on its chemical composition and on its physical properties, such as the particle size and surface characteristics [23][24][25][26].…”
Section: Near-infrared Spectroscopy (Nir)mentioning
confidence: 99%
“…Porém a maior parte da literatura disponível trata de aplicações da espectroscopia por reflexão difusa no infravermelho próximo na quantificação de ingredientes ativos, sendo a maior parte dos trabalhos aplicada ao produto final ( [42]; [43]; [44]; [45]; [46]; [47]; [48]; [40]). …”
Section: ) Espectroscopia No Infravermelhounclassified